(untitled) (Fiep Bulletin - online, 2014)
The implantation of the masters degree in the area of Physical Education, happened in the decade of 70 of the century XX, it made possible the a research perspective that became hegemonic and it received the military governments’ special attention. That direction was ruled by conceptions of science mattered and guided for the control of the physiologic parameters and linked mechanical to the sport and the physical activity. Before the exposed, the mark of that rehearsal refers the accomplishment of an analysis of the historical process of implantation and of statement of the masters degree in the area of Physical Education and it relationship with the military governments’ education politics. It is sought, also, to identify the influence and the incorporation of the American model of masters degree. In order to reach the proposed objectives, a theoreticalmethodological perspective is adopted based in the analytical categories of the historical and dialetic materialism with the intention of apprehending the relationship dialectics between the general and the matter, crossed for the historical exam of the documental sources. Like this, it opted for the use of the categories, "State", "historical block", "hegemony" and the thinker’s Antonio Gramsci "ideology" and "block of power" of theoretical Nico Poulantzas. It was verified that the implantation of the masters degree in the area of Physical Education adopted the same logic of the military governments’ education project and it served to the interests of the national sporting system. As the structure and organization of the masters degree programs, was verified the incorporation of the model and the adhesion the conception of science and practice of research of line hegemonic positivist in the United States. The direction given an area was rendered by the consent and service of the several actors’ linked social area interest, above all intellectuals, leaders of superior schools and teachers. Finally, it stands out the creation, no expected, of fundamental against-hegemony spaces to the development of a critical tendency of research in Physical Education in the country.